Co-benefits effect of non-pharmacological intervention against COVID-19 on tuberculosis in Ningxia Hui Autonomous Region: a SARIMA analysis - Ruo-nan WANG; Zheng-gui YANG; Wei-chen LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the influence of non-pharmacological interventions (NPIs) against coronavirus disease 2019 (COVID-19) on tuberculosis (TB) incidence in Ningxia Hui Autonomous Region (Ningxia) in 2020. MethodsUsing TB incidents reported in Ningxia during 2004 - 2018 as a training set and those during 2019 - 2020 as a prediction set, a seasonal autoregressive moving average (SARIMA) model was established to predict TB incidents during the three COVID-19 epidemic periods with different response level in 2020 in Ningxia. The relative rate of change in the number of TB incidence for the three response periods were calculated by comparing the TB incidence number in the COVID-19 response periods with the number of same periods in 2019 or the number predicted based on the established SARIMA model. Results The established ARIMA(1,1,2) (1,1,2)12 model was fitted to the data well, with a root mean square error of 1280.50 and a mean absolute percentage error of 13.15%. The NPIs against COVID-19 showed an inhibitive co-benefits effect on the incidence of TB in Ningxia, resulting the expected incidence reductions of 63.58%, 29.61% and 8.59% for the response periods of level I, level II and level III, respectively. ConclusionNon-pharmacological interventions against COVID-19 could exert an incidence reduction co-benefits effect on TB in Ningxia, and the effect may be positively related to the grade of emergency response.